1987
DOI: 10.1161/01.res.61.2.181
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for increased media thickness, increased neuronal amine uptake, and depressed excitation--contraction coupling in isolated resistance vessels from essential hypertensives.

Abstract: The functional and morphologic characteristics of isolated subcutaneous resistance vessels (about 170 fitn i.d.) from 15 untreated subjects with essential hypertension and 15 matched controls were examined. The vessels from the hypertensives had a 29% increase in the media-thickness-to-lumendiameter ratio. The maximal force development to noradrenaline (NA) expressed as active pressure (an estimate of the pressure the vessels could have contracted against in vivo) was 30 % higher in vessels from the hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
168
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(182 citation statements)
references
References 22 publications
12
168
2
Order By: Relevance
“…2 Small arteries 65 to 230 m were dissected from the tissue and carefully cleaned under a dissecting microscope. Isolated vessels were then transferred to an arteriographic bath chamber (Living Systems Instruments) 6 and cannulated as described previously.…”
Section: Pressure Myographymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Small arteries 65 to 230 m were dissected from the tissue and carefully cleaned under a dissecting microscope. Isolated vessels were then transferred to an arteriographic bath chamber (Living Systems Instruments) 6 and cannulated as described previously.…”
Section: Pressure Myographymentioning
confidence: 99%
“…1 However, studies in type 2D are fraught with difficulty, given the recognized associations with hypertension and dyslipidemia, both of which are known to influence small-artery structure and function. 2,3 Recently, Rizzoni et al 4 reported that small arteries of patients with type 2D have an increased media thickness to lumen diameter ratio compared with vessels from control subjects: This appeared to be due to a combination of remodeling and hypertrophy. A similar structural change was observed in patients with type 2D and hypertension (type 2DϩH), which contrasted with the eutrophic remodeling reported in patients with essential hypertension (EH).…”
mentioning
confidence: 99%
“…10,11 Small arteries, with an estimated diameter of 100 to 300 m, were dissected from the biopsy specimen and 2 artery segments were mounted as ring preparations in a myograph. 10 Lumen diameter and media thickness were measured in a standardized way as previously described. 10 …”
Section: Resistance Artery Structurementioning
confidence: 99%
“…10 Lumen diameter and media thickness were measured in a standardized way as previously described. 10 …”
Section: Resistance Artery Structurementioning
confidence: 99%
See 1 more Smart Citation